Characteristic and Mean Load Factor of NW Type Compound Planetary Gear Drive - Li Zhaogang; Liao Mingjian; Zhao Ying (Jixie chuandong)
A brief analysis of the characteristic of the compound planetary gear technology is carried out,and the performance and the values of the mean load factor of the compound planetary are discussed. The calculation method of the maximum phase difference of the meshing points and the calculation method of mean load share performance for turning angle are put forward. In a compound planetary,there is a certain amount of floating in the inner gear ring,except for the float of the sun,the connecting segments of the twin planetary shaft,inner gear ring and the spindle produce certain torsional deformations. Through numerical examples illustrate that the torsional deformations of the sun and inner gear are more than simple planetary,the compensation manufacturing deviation caused by the uneven load ability is stronger,so there will be a lower mean load factor.According to theoretical analysis and test data which has been obtained and the successful application of actual design,it is appropriate to take 1. 10 as the planetary mean load factor of the compound planetary of four planets in the design of wind power gear.